ENHANCING ENERGY EFFICIENCY IN MULTI-APARTMENT RESIDENTIAL COMPLEXES THROUGH INTELLIGENT BUILDING MANAGEMENT SYSTEMS OPERATED BY SERVICE MANAGEMENT COMPANIES - Adilova , Madina; Khusainova , Gulhayo (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article examines the issues of improving the energy efficiency of management service company (MSC) buildings within multi-apartment residential complexes through the implementation of intelligent management systems. The study analyzes modern smart technologies, including automated control systems, sensor-based monitoring tools, and digital control of engineering communications. In addition, the principles of integrating energy-efficient solutions into the functional and architectural planning of MSC buildings are considered.Based on the analysis of international experience, the effectiveness of intelligent management systems is evaluated, and the prospects for their application in the context of Uzbekistan are substantiated. As a result, architectural and technological proposals aimed at rational use of energy resources, reduction of operational costs, and optimization of management processes in MSC buildings are developed.